Spectrophotometric Determination of Strontium in Tea Leaf Sample - Zhai, Qing-Zhou (Asian Journal of Chemistry, 2010)
The optimum colour conditions of strontium(II) with p-acetylarsenazo were studied and the colour system has been successfully used in the deternination of strontium content in tea leaf sample. In a NH3-NH4Cl buffer medium of pH 10.39, strontium(II) and p-acetylarsenazo formed a blue complex of 1:2. The maximium absorption wavelength of the complex is 644 nm. A good linearity is presented between the concentration range of 0.3-4.5 μg/mL of strontium(II) and absorbance (A) and its linear regression equation is:A = 0.123C (C: μg/mL) + 0.0317, with a regression coefficient of 0.9961. The apparent molar absorption coefficient is 1.38 × 104 L mol-1 cm-1 at 644 nm. Detection limit of the method is 0.083 μg/mL.